Fecal indicators in drinking water at Juarez Valley - Flores-Márgez, Juan Pedro (REVISTA TERRA LATINOAMERICANA, 2013)
The population of Juárez Valley, Chihuahua, has a high incidence of gastrointestinal parasites. For this reason, this study was conducted to determine the microbiological quality of drinking water as one of the possible factors that disseminate pathogens. Sanitary quality of drinking water from wells was determined in 14 rural communities of the Juarez Valley through the use of indicator microorganisms. The parasites Cryptosporidium parvum and Giardia lamblia were detected by an immunomagnetic separation technique followed by an inmunofluorescence method to identify and count them. Coliform bacteria and fecal bacteria E. coli were isolated and detected by the membrane filtration method. A total of 92.8% of the sites evaluated evidenced the presence of coliforms in water samples. These samples, however, were negative for E. coli, which means there is no fecal contamination. Also, the presence of Cryptosporidium and Giardia oocysts were detected in water from 92.3% of the sites. These results suggest the need to promote mechanisms of quality control and processing of water in the communities considered in this study since chlorination has not been effective. Intensified surveillance is required in the water distribution network to reduce incidence of gastrointestinal diseases.